Regulation of PBX3 expression by androgen and Let-7d in prostate cancer - Håkon Ramberg; Ayham Alshbib; Viktor Berge; Aud Svindland; Kristin Austlid Taskén (2011)
Abstract Background The pre-leukemia transcription factor 3 (PBX) is part of the PBX family of transcription factors, which is known to regulate genes involved in differentiation of urogenital organs and steroidogenesis. This is of interest with regard to prostate cancer progression as regulation of steroidogenesis is one of the mechanisms involved in the development of castration-resistant prostate cancer. In light of this we wanted to investigate the possible involvement of androgen regulation of PBX3 expression in prostate cancer. Results In this study, we show that PBX3 is post-transcriptionally regulated by androgen in prostate cancer cells and that the effect might be independent of the androgen receptor. Furthermore, PBX3 was identified as a target of Let-7d, an androgen regulated microRNA. Let-7d was down-regulated in malignant compared to benign prostate tissue, whereas up-regulation of PBX3 expression was observed. Conclusions We demonstrate that PBX3 is up-regulated in prostate cancer and post- transcriptionally regulated by androgen through Let-7d.